2008
DOI: 10.1021/ma801199j
|View full text |Cite
|
Sign up to set email alerts
|

On the Adsorption of Two-State Polymers

Abstract: Monte Carlo(MC) simulations produce evidence that annealed copolymers incorporating two interconverting monomers, P and H, adsorb as homopolymers with an effective adsorption energy per monomer, ǫ ef f , that depends on the PH equilibrium constants in the bulk and at the surface.The cross-over exponent, Φ, is unmodified. The MC results on the overall PH ratio, the PH ratio at the surface and in the bulk as well as the number of adsorbed monomers are in quantitative agreement with this hypothesis and the theore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Physically, annealed disorder means that the type of any monomer (and its affinity to the surface, in our case) may change while the system attains its equilibrium state [33]. The annealed approximation can roughly be considered as the "zero order" approach to the problem of carrying out a quenched average.…”
Section: B Disorder Average and Morita Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…Physically, annealed disorder means that the type of any monomer (and its affinity to the surface, in our case) may change while the system attains its equilibrium state [33]. The annealed approximation can roughly be considered as the "zero order" approach to the problem of carrying out a quenched average.…”
Section: B Disorder Average and Morita Approximationmentioning
confidence: 99%
“…This is done in Section II C. An additional motivation for treating the annealed case in detail is that there is a class of so called two-state or annealed copolymers, which are adequately described by the annealed approximation (see Ref. [33] and references therein). The generalisation to the Morita approximation in Section II C is quite simple and transparent.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulations of such systems8 have been mainly devoted to the transition from a weak to strong adsorption regime, the scaling properties, the dynamics,9, 10 the influence of the internal macromolecular architecture11 and phase transitions 12–16. Adsorbed heteropolymers17–19 and proteins20 have been recently studied theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to [31], in the present work we have gone beyond the transition point and studied the temperature dependences of various observables for the annealed symmetric system. This choice was motivated for several reasons: The annealed approximation provides a zero-order rough approximation to a realistic quenched system; on the other hand, it can serve as a prototype of real physical systems like two-state polymers [39]. The system was chosen to be "twofold" symmetric: with respect to the composition of the RC and RS and with respect to the interaction map (good attractive Aa and Bb contacts had the same energy, while both bad Ab and Ba contacts were equally neutral).…”
Section: Discussionmentioning
confidence: 99%
“…Yoshinaga et al [39] developed a theory of adsorption of the so-called two-state polymers consisting of monomer units that can change its type (i.e., its affinity to the substrate or its hydrophobicity/hydrophilicity). The authors of [39] showed the equivalence of the two-state polymer to the annealed two-letter RC and established the correspondence between the RC parameters (a priori probabilities to find a monomer of a certain type in the RC sequence) and standard chemical potentials of monomers in the bulk and at the surface. Another situation that can be described in terms of the annealed approximation was suggested in [38]: the annealed RC can be viewed as a homopolymer consisting of monomer units that can adsorb small molecules, like surfactants [40], from the solution.…”
Section: Introductionmentioning
confidence: 99%